Ijtihad Sebagai Problem Solving Polemik Sistem Ekonomi Islam Kontemporer - Mugni Muhit; Rani Mariana; Ahmad Hasan Ridwan; Atang Abdul Hakim (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2023)
Abstract In terms of termminology, ijtihad is an attempt to explore a law that existed at the time of the Prophet Muhammad. Until in its development, ijtihad was carried out by friends, tabi'in and later periods until now. Although during certain periods of what we know as the taklid period, ijtihad was not permitted, during certain periods (revival or renewal), ijtihad began to be reopened. Because it cannot be denied, ijtihad is a must, to respond to life's increasingly complex challenges. Not all results of ijtihad are updates to old ijtihad because there are times when the results of new ijtihad are the same as the results of the old ijtihad. Even if the results of the new ijtihad are different, it cannot change the status of the old ijtihad. This is in line with the rules of ijtihad which cannot be canceled by ijtihad either. Based on the implementation of ijtihad that the source of Islamic law guides Muslims to understand it. The sources of Islamic law agreed upon by the majority of scholars are the Koran, hadith, ijma and qiyas (muttafaq).